The Instrumental Sense: A Netnographic Framework for Understanding Digital Companionship - Souto, Gustavo Guimarães; Morimoto, Carlos Hitoshi (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC), 2026)
Large Language Models (LLMs) have become increasingly prevalent in text and speech-based interactive systems, enabling more natural interactions that foster the formation of human-AI bonds. Competing frameworks have arisen to attempt to characterize these complex interactions and relationships that users develop with AI systems. This work examines leading explanations for human-AI companionship through a netnographic analysis of online user communities and proposes a taxonomy to identify key similarities among these explanations and to demonstrate how design choices and market forces are shaping the nature of human-AI relationships.